HUBUNGAN SELF EFFICACY, MOTIVASI, DAN PROKRASTINASI AKADEMIK DENGAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP SE-KECAMATAN KRATON YOGYAKARTA - Hilda Arifani; Agustina Sri Purnami (Universitas Sarjanawiyata Tamansiswa, 2015)
This research aims to know the information abaut theÂ tendency of self efficacy, motivation, procrastination academic, and mathematics learningÂ achievement of student VIII grade SMP in subdistrict Kraton Yogyakarta and to determine the relationship of self efficacy, motivation, procrastination academic with mathematics learning achievement of student VIII grade SMP in subdistrict Kraton Yogyakarta either partially or simultaneously. This research was ex post facto. The population of this research were students VIII grade SMP in subdistrict Kraton Yogyakarta of 360 students.Â The research sample of 90 students was taken by proportional random sampling. Analysis using descriptive analysis and multiple regression analysis. The result of the data analysis in this research are : 1) self efficacy was medium; 2) motivation was high; 3) procrastination academic was medium; 4) mathematics learning achievement was medium; 5) simultaneously there was positive relationship between self efficacy and motivation also negative relationship between procrastination academic with mathematics learning achievement ( ; 6) there was positive relationship between self efficacy with mathematics learning achievement ; 7) there was positive relationship between motivation with mathematics learning achievement ; 8) there was negative between procrastination academic with mathematics learning achievement .